2018
DOI: 10.1136/bcr-2017-221450
|View full text |Cite
|
Sign up to set email alerts
|

Relevance of enlarged cardiophrenic lymph nodes in determining prognosis of patients with advanced ovarian cancer

Abstract: Ovarian cancer often presents at an advanced stage with widespread peritoneal and/or extra-abdominal metastases. Complete cytoreduction is the mainstay of treatment for disease confined to peritoneum. But in patients with distant metastases, the role and rationale is less obvious. One of the the most common sites of extra-abdominal disease is the cardiophrenic lymph node (CPLN). In this paper, we described the management of a patient with International Federation of Gynecology and Obstetrics (FIGO) stage IVB e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 46 publications
0
7
0
Order By: Relevance
“…Peritoneal tumors, especially ovarian malignancies, preferentially metastasize to CPLNs and anterior lymphatics along the internal mammary chains (30,31). Enlarged CPLNs in advanced ovarian cancer indicate mediastinal involvement, and CPLNs are one of the most common sites of extra-abdominal spread of disease (31,32).…”
Section: Lymphatic Pathologic Conditionsmentioning
confidence: 99%
“…Peritoneal tumors, especially ovarian malignancies, preferentially metastasize to CPLNs and anterior lymphatics along the internal mammary chains (30,31). Enlarged CPLNs in advanced ovarian cancer indicate mediastinal involvement, and CPLNs are one of the most common sites of extra-abdominal spread of disease (31,32).…”
Section: Lymphatic Pathologic Conditionsmentioning
confidence: 99%
“…Thirteen articles described retrospective cohort studies [ 9 , 11 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 ], one was a case report [ 34 ], and one a case series [ 35 ]. The studies spanned the period from 1997 to 2020.…”
Section: Resultsmentioning
confidence: 99%
“…Regarding the impact of CPLN resection during cytoreductive surgery, nine studies reported the mean size of preoperative suspicious nodes [ 11 , 23 , 24 , 25 , 26 , 28 , 29 , 32 , 34 ]. The baseline characteristics are presented in Table 2 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations